mSphere of Influence: 3-D Culture Models Influence Studies on Epstein-Barr Virus Molecular Pathogenesis in the Epithelium - K. H. Y. Shair (American Society for Microbiology, 2020)
ABSTRACT Kathy Shair works in the field of Epstein-Barr virus (EBV)-associated cancers, with emphasis on nasopharyngeal carcinoma (NPC). In this mSphere of Influence article, she reflects on how the paper “Efficient replication of Epstein-Barr virus in stratified epithelium in vitro” by Temple et al. (R. M. Temple, J. Zhu, L. Budgeon, N. D. Christensen, et al., Proc Natl Acad Sci U S A 111:16544–16549, 2014, https://doi.org/10.1073/pnas.1400818111) has influenced her work on EBV molecular pathogenesis in the nasopharynx by highlighting the importance of using three-dimensional (3-D) culture models to study epithelial infection.